2022
DOI: 10.1177/09544089211070667
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nonlinear radiation on magnetohydrodynamic flow of hybrid nanofluid with heat source effect

Abstract: This investigation is performed to deliberate the novel significance of nonlinear thermal radiation effect on magnetohydrodynamic flow of Casson hybrid nanoliquid caused by a curved stretching sheet. The flow and thermal transport nature of three different hybrid nanoliquids in the stimulus of viscous dissipation, nonlinear radiation and magnetic force is discussed numerically. The novelty of this work is to obtain the simultaneous solutions for three different types of hybrid nanoliquids, they are obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Interaction of thermal radiation on the natural convective flow via a cone by analyzing the properties of wall heat, as well as mass flux through a porous medium, was presented by Ghoneim et al 20 Tassaddiq et al 21 have studied the heat and mass transfer of hybrid nanofluid through a rotating disk. The Runge–Kutta method is an effective method for solving fluid flow problems which can be seen in the following papers 22–27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction of thermal radiation on the natural convective flow via a cone by analyzing the properties of wall heat, as well as mass flux through a porous medium, was presented by Ghoneim et al 20 Tassaddiq et al 21 have studied the heat and mass transfer of hybrid nanofluid through a rotating disk. The Runge–Kutta method is an effective method for solving fluid flow problems which can be seen in the following papers 22–27 …”
Section: Introductionmentioning
confidence: 99%
“…The Runge-Kutta method is an effective method for solving fluid flow problems which can be seen in the following papers. [22][23][24][25][26][27] The fluid flows on a cone-shaped physique through a porous medium have inspired attention due to recent improvements in innovative technologies. Excellent applications for the effect of porous media may be found in a wide range of technical and industrial domains, including fiber spinning process, paper production, underground spreading of chemical waste, and nuclear waste repository.…”
Section: Introductionmentioning
confidence: 99%
“…The oblique MHD nanoliquid flow past a nonlinear stretched cylinder is reported by Abbas et al 4 Vaidya et al 5 scrutinized the mixed convective MHD flow of nanoliquid toward a Riga sheet with a chemical reaction. The electrically conducting Jeffrey nanoliquid stream by perpendicular stretching cylinder is elucidated by Hayat et al 6 Sandeep et al 7 illustrated the influence of nonlinear radiative heat on MHD hybrid nanoliquid flow past an elongated surface. Sulochana and Mahalaximi 8 investigated the influence of chemical response as well as radiative heat on the flow of Williamson nanoliquid across an expandable sheet.…”
Section: Introductionmentioning
confidence: 99%
“…As depicted by Usman et al 9 the hybrid nanoparticles have superior thermal flow rate in comparison of nanofluid. Sundaeep et al 10 have deliberated influence of nonlinear thermal radiations upon MHD hybrid nanofluid flow subject to effects of heat source on a curved stretching sheet. Ashwinkumar et al 11 have deliberated convective thermal flow in MHD hybrid nanoparticles using two different geometrical views and have concluded that augmentation in thermal radiation factor and nanoparticles concentration have boosted the distributions of temperature.…”
Section: Introductionmentioning
confidence: 99%